Pemberdayaan Ibu-Ibu Rumah Tangga Dalam Upaya Meningkatkan Ekonomi Keluarga Melalui Pengolahan Keripik Gedebog Pisang - Margarethy Rohanie Mbado; Norci Beeh; Alya Elita Sjioen; Roby Yusuf Bekuliu (Jurnal Pengabdian Masyarakat, 2024)
Poverty is one of the major problems faced by Indonesia because human needs and desires are increasing and becoming more diverse from day to day, as are household needs. One indicator for increasing welfare is by increasing empowerment of women, especially housewives. Through productive household business activities such as producing chips from banana stems, Business opportunities selling home-cooked food or chips from banana stems are still very much in demand among the community, besides this business is also not difficult to do because housewives can do this activity in the gaps of being busy as housewives, and the raw materials do not have to be bought again at the traditional market because they are already available in the garden or in the yard. Banana plants only bear fruit once and then die so the banana plants that have been harvested will be cut down and replaced with new banana shoots. Banana stems that come from the remaining harvest are usually not used or processed so that they pile up and cause an unpleasant odor for the community. In fact, banana stems have good content for the human body such as being able to prevent an increase in blood sugar levels and improve the digestive system by having daily fiber intake, banana stems can also support diet programs because they can make you full, banana hearts can also reduce postpartum fever, treat intestinal ulcers, treat chicken pox, can prevent kidney stones, reduce stomach acidity levels, and cure infections, and there are many more benefits of banana stems that are not yet known by the community